IMPLEMENTASI KONSEP BIOMEKANIKA PADA PEMBELAJARAN TEKNIK DASAR SEPAK BOLA DI SEKOLAH MENENGAH - Ahmad Mursyidin Mursyidin; Fatmasari Fatmasari; Adnan Annur; Muh. Yunus Yunus; Muh. Akbar Al Farisi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of biomechanical concepts in teaching basic football techniques in secondary schools. Biomechanics is used to help students understand the principles of body movement in performing basic techniques such as passing, dribbling, and shooting. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation during physical education learning activities. The results show that the application of biomechanical concepts helps students understand body position, balance, movement angles, and body coordination in performing basic football techniques. Students are able to correct their movement errors and improve their technical skills. Biomechanics-based learning also makes the learning process more meaningful because students do not only imitate movements but also understand the scientific principles behind each technique.